Discussion (Scottish Historical and Archaeological Internet Reports, 2004)
The date for exploitation of the quarry vein is broad - Neolithic to Bronze Age and possibly into the early Iron Age. Future examination of nearby structures might help refine this. The quarrying of quartz is compared to quarrying of other lithic raw materials. The relationship between quartz sources and settlements is considered along with ownership of/access to quartz sources and quartz exchange.